2019
DOI: 10.3892/ol.2019.10216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the effect of epidural anesthesia combined with epidural analgesia and general anesthesia combined with intravenous analgesia on prognosis of ovarian cancer patients

Abstract: Application value of epidural anesthesia combined with epidural analgesia and general anesthesia combined with intravenous analgesia in ovarian cancer surgery was explored. In total 298 ASA I–III grade patients with ovarian cancer, undergoing extensive total hysterectomy and pelvic lymphotomy, were retrospectively analyzed. Patients were divided into two groups: the epidural anesthesia combined with epidural analgesia group (group A, 158 cases), and the general anesthesia combined with intravenous analgesia gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Past studies have shown both increase and decrease in CRP levels with the type of anesthetic agents used during the surgery, or with the post-operative analgesics, anti-hypertensives, beta-blockers etc. [ 23 ], [ 24 ], [ 25 ], [ 26 ], [ 27 ]. As this variable represents a proportional change we can hypothesize that it is less affected by the differences in operative and perioperative care.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown both increase and decrease in CRP levels with the type of anesthetic agents used during the surgery, or with the post-operative analgesics, anti-hypertensives, beta-blockers etc. [ 23 ], [ 24 ], [ 25 ], [ 26 ], [ 27 ]. As this variable represents a proportional change we can hypothesize that it is less affected by the differences in operative and perioperative care.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer patients with ascites carry a significant risk of morbidity and mortality. Therefore, intraoperative fluid therapy is important for both surveillance and prevention of postoperative complications 21 . Amir et al reported that increased intraoperative blood loss and preoperative ascitic fluid amounts increased the duration of postoperative ICU stay and that the operation times were similar in patients admitted to the service or ICU 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size is determined based on the results of a literature review and pretrial, 23 24 and 552 patients will be included in this study. This sample size is based on the following statistical considerations: the primary outcome hypothesis was that patients with gynaecological oncology were non-inferior to patients with self-fatigue assessment in early postoperative ambulation in terms of time to first postoperative flatus compared with patients with fixed activity distance assessment.…”
Section: Methods and Analysismentioning
confidence: 99%